MAKNA LEKSIKAL DAN MAKNA GRAMATIKAL: RUWATAN, SUKERTA, DAN MURWAKALA - Rahmat R (LITERASI: Indonesian Journal of Humanities, 2015)
Ruwatan is one of the cultural activities in the Javanese community that has taken place for centuries years. As a ritual activity, ruwatan is still held by most of the Java community in order to make life better. In order to make ruwatan activities not to be forgotten, then it is presented a study in linguistic meaning of the word ruwatan, sukerta, and Murwakala. Data were collected from a number of sources such as research results, journals, seminars, and books. Data about the three words were then analyzed their lexical and grammatical meanings. Broadly speaking, ruwatan means an activity within the framework of self-liberation from all kinds of life problems by means of selected instruments, sukerta is object purified ie those which are considered to bear a matter of life, disruption, or bad luck, and murwakala is a tool in ruwatan that in the form of puppet shadow performance with figure of Batara Kala as an incarnation of wrong kama who will eats humans. Batara Kala will be eradicated by a character named World Sweeper.Keywords: ruwatan, sukerta, murwakala, Javanese community